2006
DOI: 10.1080/09297040600806086
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation into the Relationship Among ADHD Symptomatology, Creativity, and Neuropsychological Functioning in Children

Abstract: ADHD, creativity, behavior and cognitive functioning 1 RUNNING HEAD: ADHD, creativity, behavior and cognitive functioning.An investigation into the relationship among ADHD symptomatology, creativity, and neuropsychological functioning in children. Key words: ADHD, creativity, behavior and cognitive functioning.ADHD, creativity, behavior and cognitive functioning 3An investigation into the relationship among ADHD symptomatology, creativity, and neuropsychological functioning in children.Both creativity and Att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(48 citation statements)
references
References 34 publications
3
44
0
1
Order By: Relevance
“…Samples ascertained for high creativity have also reported increased ADHD symptoms [Cramond, 1994;Healey and Rucklidge, 2006]; 40% of children with high creativity displayed clinically significant levels of ADHD [Healey and Rucklidge, 2006]. However, in the Healey and Rucklidge study, none of these children were actually diagnosable because information from semistructured interviews indicated that they were not sufficiently functionally impaired.…”
Section: Characteristics Of the Population With Adhd And High Iq/giftmentioning
confidence: 92%
“…Samples ascertained for high creativity have also reported increased ADHD symptoms [Cramond, 1994;Healey and Rucklidge, 2006]; 40% of children with high creativity displayed clinically significant levels of ADHD [Healey and Rucklidge, 2006]. However, in the Healey and Rucklidge study, none of these children were actually diagnosable because information from semistructured interviews indicated that they were not sufficiently functionally impaired.…”
Section: Characteristics Of the Population With Adhd And High Iq/giftmentioning
confidence: 92%
“…In addition, ADHD is associated with an increased risk for other neurodevelopmental and psychiatric conditions [11,12], poorer quality of life [13], and premature mortality [14]. Despite these negative outcomes in individual functioning, reports also suggest that there may be specific strengths related to ADHD, such as creativity and hyperfocusing [15,16], although these have not been documented consistently by research [17,18]. Other studies have found certain personality features, such as inspiration and feelings of togetherness, to facilitate coping strategies in individuals with ADHD [19].…”
Section: Introductionmentioning
confidence: 99%
“…Psychiatric symptoms (e.g., elevated creativity) that cluster with specific psychiatric conditions (e.g., bipolar disorder, depression, substance use conditions, and ADHD) (Andreasen 1987, Healey and Rucklidge 2006Ludwig 1992;Post 1994Post , 1996 may be particularly relevant to entrepreneurship. As the wealth of nations has come to depend upon citizens with a wealth of notions, an elite Bcreative class^has emerged (Florida 2002).…”
Section: How Psychiatric Disorders Interact With Personality Traitsmentioning
confidence: 99%
“…Researchers have identified a relationship between creativity and psychiatric conditions including psychosis (Kyaga et al 2011(Kyaga et al , 2013Ludwig 1992), bipolar disorder (Andreasen 2008;Jamison 1995;Kyaga et al 2011;Richards et al 1988;Santosa et al 2007;Simeonova et al 2005), depression (Andreasen 2008;Ludwig 1992), ADHD (Healey and Rucklidge 2006), and substance abuse (Kyaga et al 2013;Ludwig 1992;Post 1994Post , 1996. Fluctuations in creativity and creative output correspond to fluctuations in mood (Jamison 1995).…”
Section: Creativity and Innovativenessmentioning
confidence: 99%